El contrato de seguro ante los avances en medicina y tecnología sanitaria - Benito Osma, Félix; Universidad Carlos III de Madrid (Pontificia Universidad Javeriana, 2015)
Scientific and technological advances in medicine relate to predictive or diagnostic tests (biomarkers, sensors) and treatment (robotic surgery, gene therapy) can lead to a paradigm shift in the provision of health service to tackle bigger SXXI challenges arising from the aging population, the impact of chronic diseases, mobility of patients and health professionals, as well as the reduction of available resources.Traditionally, health insurance offers insured health care within the medical team agreed with the insurer, unless of free choice, in which it assumes the reimbursement of the costs incurred in accordance with the limits in the policy . At the moment, you can consider whether we are temporarily in a curative medicine that materializes when the disease happens to a preventive and regenerative medicine which is ahead of that that occurs or develops.This scientific and technological revolution that has produced each day that the insurance has to make efforts to adapt to the present and future risks, particularly health insurance, and obligations of the parties.Health care insurance are carried by the current technology. The purpose of this insurance is to provide health care or reimburse medical costs of illness of the insured. We could say that this object, it is not so much because predictability and disease prevention, as insured risk, can occupy a privileged place. Thus, this service appears in the current insurance policies as an option can be incorporated in the policy itself,even marketed complementary.Finally, the use of all knowledge, data, tools, best computer and Internet-related technology applications, biotechnology and nanotechnology, to improve diagnosis, treatment, prevention and predictability of disease produces a risk scenario with ethical, bioethical and legal, particularly in the field of liability and insurance.